Sticky fingers and smudged sound: vinyl records and the mess of media hygiene. Issue 4 (8th August 2022) - Plotnick, Rachel
ABSTRACT: Looking historically at cleanliness, care practices, and accessories, this article examines how a variety of actors—from record listeners and music journalists to inventors, advertisers, and corporations—grappled with the problem of cleaning vinyl records in the pursuit of "clean sound" in the period between the 1950s and 1970s. Detailing how washing and preserving records became a commercialized, scientific, and often gendered caretaking process for collectors, the piece makes the case for studying under-explored dimensions of music production/consumption related to housekeeping, preservation, and embodied practices. To this end, the article offers the concept of "media hygiene" as a tool for initiating broader discussions in media studies about fragility and the role of mess in everyday media interactions. Thinking with media hygiene provides insight into the ways that people are encouraged to take responsibility for media technologies' lifespan.